EFEK ESTROGENIK EKSTRAK ETANOL 70% KUNYIT (Curcuma domestica VAL.) TERHADAP MENCIT (Mus musculus L.) BETINA YANG DIOVARIEKTOMI - Kusmana, Dadang; Lestari, R; Dewi, A. N.; Ratri, P. R. (Makara Journal of Science, 2007)
Estrogenic Effect of 70% Ethanol Turmeric (Curcuma domestica Val.) extract on ovariectomized Female Mice (Mus musculus L.). The influence of extract turmeric (Curcuma domestica Val.) on endometrium thickness, vaginal epithelium, mammary gland, and protein of estrogen receptor of ovariectomized mice was examined. Twenty five ovariectomized mice which were divided into five groups, were treated by ethynilestradiol (8,4 x 10-3 g), aquades (10 ml), and turmeric extract at doses 230 mg/kg b.w.; 310 mg/kg b.w.; and 390 mg/kg b.w. for eight days. At the end of experiments the mice were killed, then the uterus, vagina, and mammae were removed and the wet weight of uterus was recorded. Uterus, vagina, and mammae were examined histologically. Estrogen receptor protein from uterus were analized by using SDS-PAGE. One way anava test showed that turmeric extract at doses 310 mg/kg b.w. and 390 mg/kg b.w give estrogenic effect on vaginal ephitelium, endometrium thickness, and diametre of mammary glands. SDS-PAGE analysis showed there were differences in protein concentration between control and treatment groups which were seen in the thickness of the bands. Estrogen receptor band could be detected in sampel of treatment groups at molecular weight 45 kDa